ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI KERJA PADA SATPAM UNIVERSITAS DIPONEGORO KAMPUS TEMBALANG - Nabilah Rizky Khairani; Ida Wahyuni; Siswi Jayanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
The Management who directing through motivation will create good working condition. Motivation will make their workers doing their job harder by their superior toward sucessfullly. The beginning survey result of Security Guards at the Tembalang Campuss of Diponegoro University telling that Salary is not equal to their work load then will impact to their performance.This research is developed in order to analize influencing factors of working motivation of the Security Guards from intrinsict factors upto extrinsict factors.This research is qualitative and descriptive. The subject of this research are 47 persons with details aas follows : 6 persons are the Main Sources of information and 2 persons are the Triangularition informan.Observation using questioners are resulting 18 feedbacks from the subject (38,3%), 16 respondents (34,0%) having high working motivation and 13 respondents (27,7%) having poor working motivation. From Deep Interview Results, motivation factors (Intrinsict) which influencing working motivation is Recognition and the work itself. Meanwhile, Maintenance factors (Extrinsict) which influencing working motivation is Salary. The researcher also recommend to give Award and Recognition to the Security Guards, giving salary details and doing side activity to kill bordom at their workplace.